The Algorithms Are Thinking About You Right Now: A lexicon of terms from the intersection of political theory and artificial intelligence. - Srivastava, Swati (Humanities)
The article discusses the role of artificial intelligence in contemporary political systems. It is noted that government and commercial entities use machine-learning algorithms to model predictions for everyday decisions in various domains. It is noted that algorithms converts individual experience into data, which is the most valuable global commodity.